P.019 Interictal burden of migraine: correlations with other measures of migraine burden and effects of galcanezumab migraine-preventive treatment. (June 2022) - Sandoe, CH; Lipton, RB; Buse, DC; Ford, JH; Hand, AL; Jedynak, JP; Port, MD; Detke, HC
Abstract : Background: Typical migraine clinical trial endpoints assess only ictal burden. Methods: Adults (N=462) with episodic or chronic migraine with previous failure of 2-4 preventive medication categories were randomized 1:1 to 3-month double-blind treatment with placebo or galcanezumab 120mg. Primary endpoint was mean change from baseline in monthly migraine headache days. Migraine Interictal Burden Scale-4 (MIBS-4) measured migraine-related burden on non-headache days for past 4 weeks (0=no burden, 1-2=mild, 3-4=moderate, 5-12=severe). Migraine Disability Assessment (MIDAS), Migraine-Specific Quality of Life Questionnaire (MSQ), Patient Global Impression-Severity (PGI-S), depression (Patient Health Questionaire-9 [PHQ-9]), and anxiety (Generalized Anxiety Disorder Scale [GAD-7]) were assessed. Relationships among measures were assessed at baseline using Spearman's rank correlation coefficient. Results: MIBS-4 was moderately correlated with PHQ-9 (r=.55) and MSQ total (r=−.53). Other correlations with MIBS-4 were low (GAD-7, r=0.42; MIDAS, r=0.41; PGI-S, r=0.32) or negligible (migraine headache days, r=0.22). After 3 months, from a mean baseline of 13.2 monthly migraine headache days, galcanezumab patients improved by 4.4 vs 1.3 days for placebo (p<.0001). From mean MIBS-4 baseline of 5.5, galcanezumab patients improved by 1.8 vs 0.8 points for placebo (p<.0001). Conclusions: Galcanezumab significantly reduced ictal and interictal burden of migraine. Results suggest interictal burden is a distinct effect of the disease.